Factors Affecting Body Image in Adulthood: A Systematic Review - Annikmatul Karimah; Muhammad Putra Bayu Sutaata; Nida Hasanati (Research Psychologie, Orientation et Conseil, 2024)
Body image refers to the perception of various aspects regarding one's body shape, particularly physical appearance. This systematic review aims to analyze 15 international journals concerning factors that affect body image in adulthood. The results of this systematic review indicate that the factors affecting body image can have significant impacts on an individual's physical and psychological well-being during adulthood. Various factors affecting body image include peer pressure, cultural norms, high expectations, anxiety and dissatisfaction, social media pressure related to beauty standards, social views on the body, and obesity. These impacts can affect psychological well-being, leading to stress, self-esteem issues, eating disorders, depression, and low confidence levels.